Международное морское пиратство - Kudlaeva I. O. (Студенческая наука XXI века, 2016)
In this article the author examines the main aspects and the gaps in the fight against this problem as an international maritime piracy.
Keywords: уголовное право; международное морское пиратство; International maritime piracy; criminal law